The Current Status of Social Entrepreneurship Activity among Public University Students in Malaysia: Empirical Study - Nor Suhaida Bt AWANG; Wan Fauziah Bt WAN YUSOFF; Raudah Bt MOHD ADNAN (Communications of International Proceedings, 2020)
The main goal of this study was to identify the level of human capital among public university students who involved in social entrepreneurship activities in Malaysia. This study was conducted using a quantitative approach, where stratified random sampling was used on 797 students from three category of university (research, focus and comprehensive) who involve in social entrepreneurship activity. The data was analyzed using SPSS. This study revealed that the students who involved in social entrepreneurship activity in university shows high level of human capital. Student involvement in social entrepreneurship activities contributes to good leadership skills, social problem-solving skills, the ability to generate new ideas innovatively, creative thinking in helping to improve the socio-economic status of the less fortunate through business activities. In addition, they are also more competitive than students who are not involved in these activities. There is still not much information about current status of social entrepreneurship activity among students in Malaysia. Hopefully, this study can contribute to the new body of knowledge about current level of human capital among students who involved in social entrepreneurship activity in Malaysia.
Keywords: Social Entrepreneurship Activity; Human Capital; Public University.